2020
DOI: 10.1038/s41556-020-0472-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient generation of knock-in human organoids using homology-independent CRISPR–Cas9 precision genome editing

Abstract: rganoids can be generated by guided differentiation of induced pluripotent stem cells and embryonic stem cells, or from cells isolated from adult tissues 1 . Adult stem cell (ASC)-derived organoids are self-organizing structures that recapitulate aspects of cellular composition, three-dimensional (3D) architecture and functionality of the different epithelial tissues from which they originate, while maintaining genomic stability 2,3 . The possibility to derive organoids from genetically modified mouse lines, e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 57 publications
3
123
0
Order By: Relevance
“…This observation highlights two considerations when establishing cancer organoid cultures. Firstly, due to higher rates of cell death by mitotic catastrophes and other aberrations [40,88], cancer organoids often grow slower than normal organoids, and, secondly, many normal organoid cultures thrive under surprisingly simple growth conditions or require similar conditions as their cancerous counterparts. To avoid this, different strategies have been developed.…”
Section: Cancer Organoids and 'Living' Biobanks Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This observation highlights two considerations when establishing cancer organoid cultures. Firstly, due to higher rates of cell death by mitotic catastrophes and other aberrations [40,88], cancer organoids often grow slower than normal organoids, and, secondly, many normal organoid cultures thrive under surprisingly simple growth conditions or require similar conditions as their cancerous counterparts. To avoid this, different strategies have been developed.…”
Section: Cancer Organoids and 'Living' Biobanks Of Cancermentioning
confidence: 99%
“…Comparative mutational analysis of organoid cultures generated from different murine and human tissues further demonstrated that tissue-specific mutational signatures can be defined using organoids [36][37][38]. In addition, organoid cultures are amenable to a wide range of experimental tools, including single-cell transcriptomics [39], gene editing and tagging [40], (whole-mount) imaging [41], xenotransplantation [42], and co-culture with other cells such as immune cells (reviewed in [43]). Another complementary approach is to generate organoids using pluripotent stem cells (PSCs), namely embryonic stem cells or induced pluripotent stem cells (iPSCs) (reviewed in [12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…The same holds for CRISPR-based approaches and, by slightly changing the design of the donor DNA, NHEJ-based editing has been shown to efficiently produce knock-ins in dividing and non-dividing cells at base pair precision. Furthermore, this strategy, named homology-independent targeted integration (HITI), does not require homology arms and it works in vivo, producing up to 60% of correct editing [18,[46][47][48].…”
Section: Multibac and Clustered Regularly Interspaced Palindromic Repmentioning
confidence: 99%
“…To enrich the options to generate reporter cell lines and animal models, the CRISPaint system was developed to introduce reporter tags at the C-terminal coding portion of any gene of interest using a universal donor plasmid and the NHEJ pathway to repair the RGN-induced DSBs (Schmid-Burgk et al, 2016). More recently, this methodology was applied in human organoids, named CRISPR-HOT for homology-independent organoid transgenesis (Artegiani et al, 2020).…”
Section: Novel Strategies For Precise Gene Targeting In Non-dividing mentioning
confidence: 99%